Значення Шевченка для формування свідомості українських інтелігентів-постшістдесятників у Російській імперії ХІХ ст. - Харчук, Р. (Слово і Час, 2022)
У статті розглянуто значення Шевченкової поезії для формування національної свідомості покоління українських інтелігентів-постшістдесятників у Російській імперії ХІХ ст. Авторка аналізує спогади, щоденники й листування, на підставі яких робить висновок про рецепцію творчості поета Т. Зіньківським, М. Славінським, П. Тучапським,
Є. Чикаленком, Б. Грінченком, М. Грушевським, Д. Дорошенком. Із розгляду джерел особового походження випливає, що «Кобзар» був серед
лектури кожної з названих осіб. Не на всіх ця книжка справила враження в дитинстві, адже дітям було складно сприймати поезію Шевченка.
Доступ до його творчості, особливо позацензурної, також був у Росії обмеженим, але вже в дорослому віці кожен із мемуаристів визнавав Шевченків вплив на формування власної національної ідентичності. The paper deals with the perception of Shevchenko’s poetry by the generation of post-1860s
Ukrainians in the Russian Empire excluding S. Yefremov and O. Lototskyi whose stories
have been addressed in a separate study. Based on memoirs, diaries, and correspondence,
the author concludes about the influence of the poet’s work on T. Zinkivskyi, M. Slavinskyi,
P. Tuchapskyi, Ye. Chykalenko, B. Hrinchenko, M. Hrushevskyi, and D. Doroshenko.
They all had “Kobzar” among their books, while the perception of Shevchenko’s works
by them was not identical. For T. Zinkivskyi, M. Slavinskyi, and B. Hrinchenko the poet
formed the foundation of their own creativity; M. Hrushevskyi deepened his knowledge of
Shevchenko’s work under the influence of О. Konyskyi; D. Doroshenko became interested
in Shevchenko’s poetry still in childhood. Ye. Chykalenko considered Shevchenko’s work to
be insufficiently developed, as well as М. Drahomanov. P. Tuchapsky adapted Shevchenko
to socialism. Not everyone was impressed by “Kobzar” as a child due to difficulties in perceiving
Shevchenko’s poetry at an early age. The very access to his works, especially uncensored,
was also limited in Russia, but as an adult, each intellectual of the post-sixtiers (except
P. Tuchapskyi) recognized Shevchenko’s influence on the formation of his own national
identity. Although the generation of the post-sixtiers was focused mainly on politics rather
than cultural work and their circle of reading was broader than the one of their predecessors,
Shevchenko did not lose his significance for them either. The post-1860s generation also understood
the need for scholarly studies on Shevchenko’s works; in particular, V. Domanytskyi
critically examined the poet’s texts.